Analisis Yuridis atas Penundaan Pemilihan Kepala Desa (Pilkades) dalam Kerangka Hukum Administrasi Negara: Studi Kasus di Kabupaten Seruyan - Purwantoro, Erwin Agus; Farina, Thea; Nugroho, Any (Neolectura, 2025)
The postponement of Village Head Elections (Pilkades) in Seruyan Regency has caused significant legal, governance, and socio-political issues. This study analyzes the legal basis for the postponement based on Seruyan Regency Regulation No. 1 of 2016 (Perda) and its alignment with national laws, including Law No. 6 of 2014, Government Regulation No. 43 of 2014, Minister of Home Affairs Regulation No. 72 of 2020, and Law No. 3 of 2024. While Perda Seruyan No. 1 of 2016 adheres to democratic principles, it lacks specific provisions regarding postponements due to national political agendas and the extension of temporary village head terms. This gap has led to constitutional rights violations, weakened legitimacy of Acting Village Heads, stagnated village development, and potential social conflicts. This study recommends revising Perda Seruyan No. 1 of 2016 to incorporate postponement provisions, allocating Pilkades budgets in the Regional Budget (APBD), and enhancing transparency and public participation to ensure legal, transparent, and accountable Pilkades implementation, ultimately maintaining social, political, and governmental stability at the village level.